Restorative effect of audio and visual elements in urban waterfront spaces - Zhu, Guofeng; Yuan, Minmin; Ma, Hui; Luo, Zhaoxin; Shao, Shegang (Frontiers in Psychology, 2023)
Introduction Urban waterfront spaces are often composed of built infrastructures and nature elements. Though citizens could take advantage of these public spaces to relax from daily work, its restorative potential has not been paid enough attention. In this study, the restorative effect and mechanism of different audio and visual elements in urban waterfront spaces was systematically studied. Methods At the first stage, restorative potential of waterfront spaces was investigated and different elements with restorative effects were identified through an on-site survey, in which visual and auditory forms of environmental-nature, animal-nature, on-water human activities and on-shore human activities were identified. At the second stage, a series of laboratory experiments were conducted to explore the restorative function of the audio and visual elements. Results and discussion It is found that the degree of artificiality of waterfront space was a crucial factor influencing the restoration level of the space, and higher artificiality level of waterfront space resulted in lower level of perceived restoration. However it was available by adding visual and audio elements to the scene to facilitate the restorative effect in waterfront spaces with high-level artificiality. The effects of adding visual and auditory elements on psychophysiological restoration were explored, and elements that should be recommended and restrained were discussed. Prospects These findings would provide applicable suggestions for future design and rebuilding of urban waterfront spaces.